2004
DOI: 10.1159/000081643
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Hyperbaric Oxygen Therapy on Liver Regeneration after 90% Hepatectomy in Rats

Abstract: Background/Aims: Hyperbaric oxygen therapy (HBOT) has been reported to augment oxygen delivery to ischemic tissues and improve the liver dysfunction in clinical cases. HBOT was performed after 90% hepatectomy in rats to determine its effect on the regeneration of remnant liver. Methods: After 90% hepatectomy was performed in 8-week-old male Wistar rats, the animals were subdivided into an HBOT (2 atm abs., 80% O2, 1 h/day, 3 days) group and a non-HBOT group. Members of both groups were sacrificed, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
11
2
Order By: Relevance
“…Although some studies emphasize the increased speed of liver regeneration and improvement of liver function in severe situations, including hepatic artery thrombosis after transplantation, no significant alterations were seen 19 . Laboratory parameters and prognostic indices showed no significant improvement, contrary to what some authors say about the improvement of levels of some enzymes after use of hyperbaric oxygen therapy 8,14,15,18 . Also, it was not found here data changing or improving the MELD and the Child significantly.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Although some studies emphasize the increased speed of liver regeneration and improvement of liver function in severe situations, including hepatic artery thrombosis after transplantation, no significant alterations were seen 19 . Laboratory parameters and prognostic indices showed no significant improvement, contrary to what some authors say about the improvement of levels of some enzymes after use of hyperbaric oxygen therapy 8,14,15,18 . Also, it was not found here data changing or improving the MELD and the Child significantly.…”
Section: Discussioncontrasting
confidence: 72%
“…This feature has made to develop studies on the control of cell growth, as treatment of liver failure 4,11 . Among the noninvasive treatment options, hyperbaric oxygen therapy (OXTH) has been one of the most promising, and from year 1990 very well investigated 6,8,14,15,18,19 . Oxygen therapy is the inhalation of 100% oxygen at a pressure of two to three atmospheres, in special chambers, so called hyperbaric chambers 18 .…”
mentioning
confidence: 99%
“…Because it was reported that the regenerating liver required increased levels of energy charge [28], and HBO treatment improved energy metabolism after PH [24], we then analyzed the hepatic ATP levels (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…All animals were allowed free access to standard chow and water after the operation. Rats were sacrificed at various time points (24,48,72, and 96 h after PH), by puncture of the aorta and exsanguination under ether anesthesia. Liver samples were obtained, some for histological analysis and some were frozen and stored at À80°C.…”
Section: Animals and Surgerymentioning
confidence: 99%
See 1 more Smart Citation